Research on the Green Development of Space Defense System and Construction Technology of Great Walls in Shahukou. Issue 1 (February 2021) - Shang, Ruihua; Qiao, Jianfeng; Han, Pengju; Qin, Huichuan
Abstract: To study the characteristics of green development of the ancient Great Walls, this paper studies the space defense system in Ming and Qing dynasties and construction technology of Shahukou by means of literature review and on-the-spot investigation. The conclusions are as follows. The ancient Great Walls in Shahukou is a large and deep spatial structure which composes of Shahukou pass of Great Walls, Shahu fortress, and different types of piers. The attackers need to occupy city towers over city gates in Shahu Fortress and corner tower over Mamian pier, while the defenders need to carry out fire prevention and anti-collision work for the gate and gate hole in Shahu Fortress. Rammed materials has experienced many stages, such as ginger stone and yellow mud, grass mud, tabia, glutinous grain pulp tabia, and glutinous grain pulp mortar. Timber construction, timber component, and timber formwork were existed timber in the construction process in ancient Great Walls. The reason why large area of covered bricks lost was that a through joint was formed between the brick layer and the rammed soil.